A method of summability of Lagrange interpolation - Detlef H. Mache (International Journal of Mathematics and Mathematical Sciences)
The author uses in this paper a technique from numerical integration (see [9]) to get a discretely defined operator, which is a modification of the Lagrange operator. Therefore we improve with the linear summation method Ln* a result presented in [12] and we also point out a solution for a problem of P.L.Butzer in the proceedings of the Budapest conference in 1980.